Association of FSH receptor promoter’s polymorphisms with IVF-failure in Iranian women - Bonyadi, Khadijeh; Damavandi, Elia; Chibine, Hamid; Kabuli, Majid; Aghahosseini, Marzieh; Ghadami, Mohsen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Follicle-Stimulating Hormone Receptor (FSHR) gene shows five Single Nucleotide Polymorphisms (SNPs) in the promoter region at positions -29, -37, - 114, -123 and -138 that have been reported to be associated with higher levels of FSH and various ovarian responses to FSH in IVF (In-vitro fertilization) treatment at different populations. Hence, they are important regulators of hormone activity at the target level in IVF process. This study was performed to investigate the association between FSHR gene polymorphisms and IVF failure in Iranian women. Methods: SNPs in the promoter region of FSHR gene were analyzed by PCR and direct sequencing technique in 90 women in three equally sized groups of IVF failure, IVF success and normal fertile women, using genomic DNA extracted from white blood cells. Results: No significant differences were found in allelic variants frequency and genotype distribution between each category of subjects when analyzing the FSHR SNPs in the promoter region (p-value >0.05). However, analysis of the data revealed that the subjects with A/A genotype at the –29 position received higher amount of exogenous FSH for ovulation induction compared to G/G genotypes. Conclusions: These results indicate that the FSHR SNP at position –29 may influence sensitivity of the FSHR to FSH for ovulation induction in IVF treatment. It may be concluded that the A/A genotype at position –29 is associated with poor ovarian response to FSH so that subjects with A/A genotype at the –29 position may require higher doses of exogenous FSH for ovulation induction during IVF process.